Prinsip Moderasi Beragama Dalam Tafsir An-Nasafi - Fadhila Sidiq Permana (BASHA'IR: JURNAL STUDI AL-QUR'AN DAN TAFSIR, 2025)
Religious moderation in today's age, where conflicts often arise between groups or religions, is crucial for fostering a wise and non-extremist approach to faith. Excess in religiosity can lead to difficulties for oneself and others. Religious extremism tends to render individuals or groups incapable of objective bias, unable to be fair, and frequently discriminative towards other groups. This study selects the object of study as the exegesis of an-Nasafi, which is primarily Māturīdiyyah in orientation and has the genre of Tafsir bi al-Ra'yi, with a rational-theological pattern that is relevant for interpreting the concept of wasatiyyah impartially. Then, the method used in this study employs the Thematic Tafsir (Tafsir Maudhu'i) method with a Qualitative Content Analysis approach to the verses of moderation in Tafsir An-Nasafi. This article attempts to elucidate the importance of religious moderation and to explain the principles of religious moderation. The object of this literature research is the tafsir text an-Nasafi, where the author focuses on the verses of moderation in the Qur'an. This research draws the conclusion that in the tafsir an-Nasafi, there are two fundamental principles regarding religious moderation. The first principle is the preservation of justice (al-‘Adl), and the second principle is the effort to prevent excessive attitudes or any form of extremism (Daf’u al-Ghuluw) in ideology and religious attitudes.